PENDIDIKAN KESEHATAN DALAM PENINGKATAN PEMAHAMAN KELUARGA BERENCANA KEPADA MASYARAKAT DI DESA PENAMBANGAN SEMANDING TUBAN - rahmawati, eva silviana; Utami, Aris Puji; Nur Cholila; Nurjanah, Yumsah Amalia; Faig Yahrotus; Fitria Damayanti , Tri yunita (ABDIMASNU: Jurnal Pengabdian kepada Masyarakat, 2023)
Abstract This research is motivated by the author's interest in counseling family programsplanning in Genaharjo, Semanding District, Tuban Regency. Things that influence as well as factors examined by researchers are from factors of attitude towards acceptance of contraception in couples of childbearing age. The purpose of this research is toto determine the effect of counseling on family planning programs on the attitudes of couples of childbearing age in Genaharjo Village. This research is supported by theoretical conceptual ideas about: Attitude Concept, Population Concept, Family Planning Concept, and Counseling Concept. Family planning program counseling has a significant effecton the attitudes of couples of childbearing age. Suggestions that can be given by researchers include: 1) Expected for age couples fertile women who are participants in family planning program counseling so that they continue to attend counseling events because many benefits that can be received such as knowledge of contraceptives so that you are not mistaken inselection or use. 2) It is hoped that the BKKBD can continue to develop activitiescounseling in terms of approaches and strategies that are even better because of counselingFamily planning programs are very beneficial for couples of childbearing age. 3) For further researchers who are interested conducting research with the same study is expected to further develop research fromaspects that have not been discussed in this study.